Self-Expression and Mental Wellbeing of Malaysian Youths on Social Media - Jamilah, Maliki; Khadijah, Mohamad Tuah; Malia, Taibi; Vimala, Govindaraju; NUR SHAYKILAH, ALI OSMAN (UKM Press, 2024)
In today's fast-changing technological era, the new generation of youths, namely Gen Z and Millennials, wholeheartedly embrace and are profoundly influenced by the rapid development of social media. It is important to recognize that the impact of VUCA on youth and social media is not solely negative. It is crucial to promote digital literacy, encourage healthy online habits, and foster open conversations and self-expression. Social media platforms provide a constant stream of information, including news, opinions, and updates from friends and peers. The volatility and uncertainty of this information can contribute to feelings of overwhelm and anxiety, especially when it involves negative or distressing content. This study focuses on the use of emoticons and symbols in self-expression as well as the emotional reaction regarding one’s own posts and others. A total of 500 participants were recruited for this study from various parts of Malaysia aged between 18 to 30 years old. Descriptive analysis of the study shows majority of the participants used emoticons and symbols for better self-expression. When it comes to emotional reactions, the Gen Z and Millennials generally show a preference for positive postings. However, they also demonstrate empathy and understanding towards those who share negative postings. This study enhances our understanding of how Malaysian youths express themselves on social media and sheds light on their emotional responses.